ANALISIS KENDALA-KENDALA DALAM PENERAPAN SMM ISO 9001:2008 DI SMKN 3 WONOSARI KABUPATEN GUNUNGKIDUL - , Agung Nugroho ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research has purpose to (1) identify the barriers in applying SMM ISO 9001:2008 that need to be anticipated, (2) to analyze the effort priority of school management in anticipating the existing barriers, and (3) to recommend the alternative solution in anticipating barriers in applying SMM ISO 9001:2008 in SMKN 3 Wonosari. This is descriptive research with qualitative approach. Focus Group Discussion and questionnaire were used as data collecting method. The respondents were 8 people from school management that were taken by purposive sampling technique. The qualitative data method by Creswellâs technique and quantitative data method using Analytical Hierarchy Process which assisted by Microsoft Excell 2007 Software. Based on the result of data analysis and discussion, it was summarized that (1) the barriers in applying SMM ISO 9001:2008 in SMKN 3 Wonosari is the weakness of management commitment, the low of employee quality culture, the negative perception of employee and the lack of communication, (2) the school management priority in anticipating the existing barriers is building the commitment of togetherness (1st priority), supervising and monitoring consistently (2nd priority), doing routinely coordination (3rd priority), and increasing human resources quality (4th priority), and (3) the short term alternative solution in anticipating the barriers in applying SMM ISO 9001:2008 are reward and punishment, and socialization.